Factors Influencing Adoption of E-Banking Services in Selected Areas of Gujarat (Journal of Informatics Education and Research, 2024)
In the contemporary era, the rapid evolution of technology has ushered in a paradigm shift in the way individuals manage their financial transactions. Among the myriad advancements, the adoption of mobile banking applications stands out as a transformative force, redefining the landscape of banking services. The present study tried to study the awareness of mobile banking services of banking applications and to ascertain the factors influencing consumer behavior adoption of Mobile. Further study carried out to study the association among demographic variables regarding factors studied for consumer behaviour adoption of mobile. In conclusion, the analysis of customers' preferences underscores a moderate response to the mobile banking application. While the current features of the application are satisfactory, customers express a desire for additional features akin to those found in alternative mobile banking applications such as SBI and HDFC. The prevailing perception among customers is that the application offered by Kotak Mahindra Bank is characterized by basic and uncomplicated features. Despite this, customer satisfaction with the Mobile Banking Application remains notably high, attributed to an extensive array of features and services. This observation accentuates the importance of ongoing efforts to enhance the mobile banking application in alignment with evolving customer expectations and industry standards.